A randomised controlled trial of vitamin D and omega-3 long chain polyunsaturated fatty acids in the treatment of irritability and hyperactivity among children with autism spectrum disorder. Issue 187 (March 2019) - Mazahery, Hajar; Conlon, Cathryn A.; Beck, Kathryn L.; Mugridge, Owen; Kruger, Marlena C.; Stonehouse, Welma; Camargo, Carlos A.; Meyer, Barbara J.; Jones, Beatrix; von Hurst, Pamela R.
Highlights: Irritability and hyperactivity were common in children with ASD. Vitamin D and omega-3 reduced irritability symptoms in children with ASD. Vitamin D reduced hyperactivity symptoms in children with ASD. Abstract: Irritability and hyperactivity are common in children with Autism Spectrum Disorder (ASD). Because pharmacological treatments may have adverse effects, and despite limited evidence, caregivers/parents often use dietary supplements such as vitamin D and omega-3 fatty acids to address these behavioural symptoms. As a secondary objective of the VIDOMA (Vitamin D and Omega-3 in ASD) trial, we evaluated the efficacy of vitamin D, omega-3 long chain polyunsaturated fatty acid [omega-3 LCPUFA; docosahexaenoic acid (DHA)], or both on irritability and hyperactivity. New Zealand children with ASD (aged 2.5–8 years) participated in a 12-month randomized, double-blind, placebo-controlled trial of vitamin D (2000 IU/day, VID), omega-3 LCPUFA (722 mg/day DHA, OM), or both (2000 IU/day vitamin D + 722 mg/day DHA, VIDOM). The primary outcomes were the Aberrant Behaviour Checklist (ABC) domains of irritability and hyperactivity. Biomarkers (serum 25-hydroxyvitamin D [25(OH)D] and omega-3 index) and primary outcomes were measured at baseline and 12-months. Out of 111 children who completed baseline data collection, 66% completed the study (VID = 19, OM = 23, VIDOM = 15, placebo = 16). After 12 months, children receiving OM (-5.0 ± 5.0, P  = 0.001) and VID (-4.0±4.9, P  = 0.01) had greater reduction in irritability than placebo (0.8±6.1). Compared to placebo, children on VID also had greater reduction in hyperactivity (-5.2±6.3 vs. -0.8±5.6, P  = 0.047). Serum 25(OH)D concentration (nmol/L, mean±SD) increased by 27±14 in VID and by 36±17 in VIDOM groups ( P  < 0.0001), and omega-3 index (%, median (25th, 75th percentiles)) by 4.4 (3.3, 5.9) in OM and by 4.0 (2.0, 6.0) in VIDOM groups ( P  < 0.0001), indicating a good compliance rate. The results indicate that vitamin D and omega-3 LCPUFA reduced irritability symptoms in children with ASD. Vitamin D also reduced hyperactivity symptoms in these children.